Riscos de adoecimento, fadiga e qualidade do sono em trabalhadores de enfermagem de terapia intensiva - Nazario, Elisa Gomes (2021)
Aims: To analyze the risks of illness, fatigue and sleep quality in nursing workers in intensive care units of three university hospitals in Rio Grande do Sul. Method: Cross-sectional, correlational, multicenter study, carried out with intensive care nurses and nursing technicians from three university hospitals in southern Brazil. Data collection carried out between July/2020 and February/2021, virtually, using a sociodemographic and occupational questionnaire; Work Context Assessment Scale, Human Cost of Work Scale and Work-Related Damage Assessment Scale; Fatigue Rating Scale and Pittsburgh's Sleep Quality Index. Descriptive analysis and association analyzes were performed using the Chi-square and Fisher's exact test. Correlation analysis using Spearman's correlation coefficient, with a significance level of 5%. Results: A total of 114 workers participated, with a predominance of nursing technicians, female, with children and a partner, celetist, from children's units, from the mixed/night shift. It evidenced a predominance of critical assessment in the factors of the Work Context Assessment Scale. In the Human Cost of Work Scale, the factors physical cost and affective cost were identified, with a predominance of critical assessment, and in the factor cognitive cost severe assessment. In the Work-Related Injury Assessment Scale, critical assessment was predominant in the Physical harm factor, and in the Psychological and Social harm factor, bearable assessment. By dichotomizing the variables, it evidenced the prevalence of risk of illness related to the assessment of the Work Context and the Human Cost at Work, and the prevalence of illness in the assessment of work-related physical harm. Low fatigue predominated among workers and poor sleep quality. There was an association between physical, psychological and social illness, sleep quality and fatigue. Final considerations: Work in intensive care predisposes the nursing worker to the risk of work-related illness, with implications for the quality of sleep and fatigue. This study contributes with situational data about the work performed by nursing in this health care setting and can contribute to the planning of actions that promote workers' health.